Insights About Circadian Clock and Molecular Pathogenesis in Gliomas - Arafa, Kholoud; Emara, Marwan (Frontiers in Oncology, 2020)
The circadian clock is an endogenous time-keeping system that has been discovered across kingdoms of life. It controls and coordinates metabolism, physiology, and behavior to adapt to variations within the day and the seasonal environmental cycles driven by earth rotation. In mammals, although circadian rhythm is controlled by a set of core clock genes that are present in both in suprachiasmatic nucleus (SCN) of the hypothalamus and peripheral tissues, the generation and control of the circadian rhythm at the cellular, tissue, and organism levels occurs in a hierarchal fashion. The SCN is central pacemaker comprising the principal circadian clock that synchronizes peripheral circadian clocks to their appropriate phase. Different epidemiological studies have shown that disruption of normal circadian rhythm is implicated in increasing the risk of developing cancers. In addition, deregulated expression of clock genes has been demonstrated in various types of cancer. These findings indicate a close association between circadian clock and cancer development and progression. Here, we review different evidences of this association in relation to molecular pathogenesis in gliomas.